The role of linear pottery houses in the process of neolithisation - Pavlů, Ivan (Documenta Praehistorica, 2013)
A Linear Pottery settlement represents on a certain scale a symbiosis of different soci-economic groups of inhabitants in one given space. The role and status of artefacts can be de- scribed according to individual types of houses. Stockbreeding is typical for large houses, while small houses manifest hunting as well as breeding. Three-part houses are the most significant buil- dings as the artefact assemblages display prestigious social roles. The assemblages in the single-part houses suggest household activities.
Keywords: arheološke najdbe; ceramic; družbeni razvoj; keramika; neolitik; zgradbe